Resuspension of sediment as a method for managing shallow eutrophic lagoons - Mauro Lenzi (African Journal of Environmental Economics and Management, 2022)
The article sets out to demonstrate that resuspension of sediment could be used to counteract the consequences of eutrophication and to manage degraded coastal lagoons subject to frequent periodic dystrophic processes. This is done by a general review of the literature on resuspension of sediment, focusing on its effects in shallow eutrophic lagoons and the results of specific research recently conducted by the author.